Danish register-based study on the association between specific cardiovascular drugs and fragility fractures. Issue 12 (29th December 2015) - Torstensson, Maia; Hansen, Annette Højmann; Leth-Møller, Katja; Jørgensen, Terese Sara Høj; Sahlberg, Marie; Andersson, Charlotte; Kristensen, Karl Emil; Ryg, Jesper; Weeke, Peter; Torp-Pedersen, Christian; Gislason, Gunnar; Holm, Ellen
Abstract : Objective: To determine whether drugs used in treatment of cardiovascular diseases (CVD-drugs), including hypertension, increase the risk of fragility fractures in individuals above the age of 65 years. Design: Retrospective nationwide cohort study. Setting: Danish nationwide national registers. Participants: All individuals in Denmark ≥65 years who used specified CVD-drugs in the study period between 1999 and 2012. Main outcomes measures: Time-dependent exposure to CVD-drugs (nitrates, digoxin, thiazides, furosemide, ACE inhibitors, angiotensin receptor antagonists, β-blockers, calcium antagonists and statins) was determined by prescription claims from pharmacies. The association between use of specific CVD-drugs and fragility fractures was assessed using multivariable Poisson regression models, and adjusted incidence rate ratios (IRRs) were calculated. Results: Overall, 1 586 554 persons were included, of these 16.1% experienced a fall-related fracture. The multivariable Poisson regression analysis showed positive associations between fracture and treatment with furosemide, thiazide and digoxin. IRRs during the first 14 days of treatment were for furosemide IRR 1.74 (95% CI 1.61 to 1.89) and for thiazides IRR 1.41 (1.28 to 1.55); IRR during the first 30 days of treatment with digoxin was 1.18 (1.02 to 1.37). Conclusions: Use of furosemide, thiazides and digoxin was associated with elevated rates of fragility fractures among elderly individuals. This may warrant consideration when considering diuretic treatment of hypertension in elderly individuals.